A negative electrode material and preparation method thereof, negative electrode dry electrode sheet and aqueous battery

The carbon coverage of titanium phosphate sodium/carbon composite material is used to cover the dried method, which solves the problem of uneven wet coverage and difficulty in conductivity. Energy density and production efficiency.

CN118529707BActive Publication Date: 2025-01-28CHAOWEI POWER GROUP CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410977092.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-22
Publication Date
2025-01-28
Estimated Expiration
2044-07-22

AI Technical Summary

Technical Problem

Most existing aqueous sodium ion batteries use wet coating process, resulting in uneven coating and large amounts required to improve conductivity, resulting in a large reduction in the volume energy density of the material.

Method used

The dried method is used to cover the carbon sodium phosphate sodium/carbon composite material. By mixing high -speed titanium titanium sodium ahead and thermosetric resin, it is burned at high temperature in inert gas to obtain sodium phosphate/carbon composite material.

Benefits of technology

The close combination of carbon covering layer and negative electrode materials improves the conductivity of sodium titanium phosphate, ensures the uniformity of carbon coating, shortens the production cycle, reduces production costs, and improves the volume energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118529707B_ABST
    Figure CN118529707B_ABST
Patent Text Reader

Abstract

The present invention discloses a negative electrode material and a preparation method thereof, a negative electrode dry electrode sheet and an aqueous battery, belonging to the technical field of aqueous batteries; the present invention solves the problem that the electrodes of existing aqueous batteries are coated by wet method, the coating is uneven and the volume energy density of the material is low. The present invention provides a method for preparing a negative electrode active material, the negative electrode active material is a sodium titanium phosphate / carbon composite material, and the preparation process includes the following steps: step 1, preparing a sodium titanium phosphate precursor; step 2, coating the sodium titanium phosphate precursor with a resin; mixing the obtained sodium titanium phosphate precursor with a thermosetting resin at a high speed to obtain a resin-coated sodium titanium phosphate precursor; step 3, calcining the resin-coated sodium titanium phosphate precursor at a high temperature in an inert gas to obtain a sodium titanium phosphate / carbon composite material. The present invention improves the capacity and battery stability of aqueous batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aqueous batteries, and in particular to a negative electrode material and a preparation method thereof, a negative electrode dry-process electrode sheet and an aqueous battery. Background Art

[0002] With the growing market demand for large-scale energy storage, lithium-ion batteries have become the most widely used chemical energy storage system, but due to the shortage of lithium resources, they cannot meet the needs of large-scale applications. Developing renewable energy represented by solar and wind energy is one of the effective ways to solve this problem. Since these renewable energy sources are intermittent, large-scale grid energy storage systems are needed to store and utilize these renewable energy sources. In recent years, aqueous sodium-ion batteries (ASIBs) have become one of the most promising energy storage systems due to their abundance of sodium and the stability of aqueous electrolytes, and have received widespread attention from researchers.

[0003] Polyanion compounds have the advantages of stable structure, large ion transport channels and abundant sodium ion active sites, making them one of the most promising electrode materials for aqueous sodium ion batteries. Polyanion materials have poor conductivity, and researchers usually use a wet process to carbon-coat the materials, but this coating method takes a long time to experiment.

[0004] The electrode sheets of aqueous sodium-ion batteries are mostly prepared using traditional wet manufacturing processes. During the solvent evaporation process of wet electrodes, the binder and conductive agent will float with the solvent and gather near the surface, while the active material will precipitate, resulting in electrode stratification, which will damage the construction of the electrode conductive network and reduce the bonding strength between the active material and the current collector.

[0005] Most of the existing sodium titanium phosphate / carbon negative electrode materials used in aqueous sodium ion batteries choose graphite, conductive carbon black, sucrose, etc. as carbon sources for wet coating. This coating method is not only uneven, but also requires a large amount of material to improve its conductivity, which greatly reduces the volume energy density of the material. Summary of the invention

[0006] In view of the above analysis, the present invention aims to provide a negative electrode material and a preparation method thereof, a negative electrode dry electrode sheet and an aqueous battery, so as to solve the technical problem that most existing aqueous sodium ion batteries choose wet coating, which is not only uneven in coating, but also requires a large amount of material to improve its conductivity, thereby greatly reducing the volume energy density of the material.

[0007] The purpose of the present invention is mainly achieved through the following technical solutions:

[0008] The present invention provides a method for preparing a negative electrode active material, wherein the negative electrode active material is a sodium titanium phosphate / carbon composite material; the preparation process of the sodium titanium phosphate / carbon composite material comprises the following steps:

[0009] Step 1, preparing a sodium titanium phosphate precursor;

[0010] Step 2, coating the sodium titanium phosphate precursor with resin;

[0011] The obtained sodium titanium phosphate precursor is mixed with a thermosetting resin at a high speed to obtain a resin-coated sodium titanium phosphate precursor;

[0012] Step 3: calcining the resin-coated sodium titanium phosphate precursor in an inert gas at a high temperature to obtain a sodium titanium phosphate / carbon composite material.

[0013] Further, in step 1, the preparation process of the sodium titanium phosphate precursor includes:

[0014] The titanium source, the phosphate source and the sodium source are evenly mixed by ball milling in a molar ratio of 2:3:(1-1.05) to obtain a precursor suspension, and the precursor suspension is spray-dried to obtain a sodium titanium phosphate precursor.

[0015] Furthermore, in step 1, the solid content of the precursor suspension is 15-30%.

[0016] Furthermore, in step 1, the titanium source is one or more of titanium dioxide, tetrabutyl titanate, isopropyl titanate, titanium phosphate, and titanium tetrachloride.

[0017] Furthermore, in step 1, the phosphate source is one or more of NaH2PO4, diammonium phosphate, titanium phosphate, and phosphoric acid.

[0018] Furthermore, in step 1, the sodium source is one or more of Na2CO3, NaH2PO4, NaHCO3, and CH3COONa.

[0019] Further, in step 3, the D50 of the negative electrode active material is 4-15 μm.

[0020] On the other hand, the present invention further provides a negative electrode active material, which is prepared by the above-mentioned method for preparing the negative electrode active material.

[0021] Furthermore, the present invention also provides a negative electrode dry-process electrode sheet, which is prepared by using the negative electrode active material prepared by the above-mentioned preparation method of the negative electrode active material; or, is prepared directly by using the above-mentioned negative electrode active material.

[0022] Finally, the present invention also provides an aqueous battery, comprising the above-mentioned negative electrode dry-process electrode sheet; and also comprising a positive electrode dry-process electrode sheet, an electrolyte and a battery casing.

[0023] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0024] (1) The present invention adopts a dry coating process to carbon-coat the negative electrode material. After firing, the coating layer is tightly combined with the negative electrode material and is not easy to fall off. In addition, the present invention improves the conductivity of sodium titanium phosphate by coating the carbon layer.

[0025] (2) The present invention ensures the uniformity of carbon coating by mixing the sodium titanium phosphate precursor with the thermosetting resin at a high speed, thereby ensuring the uniformity of the carbon layer on the surface of the negative electrode material after calcination.

[0026] (3) Compared with the conventional wet electrode, the dry electrode of the present invention omits the drying and curing process, thereby shortening the production cycle and reducing the production cost.

[0027] (4) The binder in the dry electrode of the present invention exists in a fibrous state. The binder is in point contact with the surface of the active material particles only and does not affect the internal contact between the active material particles. The contact between the active material particles and between the active material particles and the conductive agent particles is closer, resulting in a smaller resistance.

[0028] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the embodiments of the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The accompanying drawings are only used for the purpose of illustrating specific embodiments and are not to be considered as limiting the present invention. In the entire drawings, the same reference symbols represent the same components;

[0030] Figure 1 is the XRD pattern of the sodium titanium phosphate / carbon composite material prepared in Example 1;

[0031] Figure 2 is a SEM image of the sodium titanium phosphate / carbon composite material prepared in Example 1;

[0032] Figure 3 This is a comparison chart of the cycle performance of an aqueous sodium ion battery composed of a dry electrode in Example 1 and an aqueous sodium ion battery composed of a dry electrode in Comparative Example 1;

[0033] Figure 4 This is a comparison chart of the cycle performance of an aqueous sodium ion battery composed of a dry electrode in Example 2 and an aqueous sodium ion battery composed of a wet electrode in Comparative Example 2;

[0034] Figure 5 This is a rate performance diagram of aqueous sodium ion batteries composed of dry electrodes of Examples 3, 4, and 5. DETAILED DESCRIPTION

[0035] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0036] In one aspect, the present invention provides a method for preparing a negative electrode active material, wherein the negative electrode active material is a sodium titanium phosphate / carbon composite material; the preparation process of the sodium titanium phosphate / carbon composite material comprises the following steps:

[0037] Step 1, preparing a sodium titanium phosphate precursor;

[0038] Step 2, coating the sodium titanium phosphate precursor with resin;

[0039] The obtained sodium titanium phosphate precursor is mixed with a thermosetting resin at a high speed to obtain a resin-coated sodium titanium phosphate precursor;

[0040] Step 3: calcining the resin-coated sodium titanium phosphate precursor in an inert gas at a high temperature to obtain a sodium titanium phosphate / carbon composite material, that is, to obtain a negative electrode active material.

[0041] In the above step 1, the preparation process of the sodium titanium phosphate precursor is: the titanium source, the phosphate source and the sodium source are evenly mixed by ball milling in a molar ratio of 2:3:(1-1.05), and a precursor suspension is obtained after the mixture is evenly mixed; wherein the solid content of the precursor suspension is 15-30%; the precursor suspension is spray dried to obtain the sodium titanium phosphate precursor.

[0042] In the above step 1, the titanium source is first ball-milled and mixed evenly, and then the sodium source and phosphate are added in sequence. This is because most titanium sources are insoluble in water. Therefore, the titanium source is added first to ensure its uniform dispersion.

[0043] In the above step 1, the molar ratio of the titanium source, the phosphate source and the sodium source is controlled within the above range, which can ensure that the atomic ratio of the synthesized sodium titanium phosphate / carbon composite material is Na:Ti:PO4=1:2:3.

[0044] In the above step 1, the titanium source is one or more of titanium dioxide, tetrabutyl titanate, isopropyl titanate, titanium phosphate, and titanium tetrachloride. The above titanium sources are used because of their good dispersibility.

[0045] In the above step 1, the phosphate source is one or two of NaH2PO4, ammonium dihydrogen phosphate, titanium phosphate, and phosphoric acid. The above phosphate sources are used because they are easy to obtain and low in cost. In the above step 1, the sodium source is one or two of Na2CO3, NaH2PO4, NaHCO3, and CH3COONa. The above sodium sources are used because they are low in cost and do not produce polluting gases. NaH2PO4 can be used as both a phosphate source and a sodium source.

[0046] In the above step 2, the sodium titanium phosphate precursor and the thermosetting resin are mixed for 10-45 min, and the stirring speed during mixing is 3000-7000 rad / min to obtain a resin-coated sodium titanium phosphate precursor.

[0047] In the above step 2, the above thermosetting resin is one or more of epoxy resin, polyester resin, vinyl resin, bismaleimide, and thermosetting polyimide, and the mass proportion of the thermosetting resin (that is, the percentage of the thermosetting resin material in the total mass of the sodium titanium phosphate precursor and the resin material) is 5%-30%, for example, 5%, 10%, 15%, 20%, 25%, 30%.

[0048] It should be noted that the use of the above-mentioned thermosetting resin as a carbon source for dry carbon coating makes the coating more uniform and compact. When the conductivity of the material is improved, the amount of carbon coated is less, so its volume energy density is higher. In addition, the mass ratio of the thermosetting resin is controlled within the above range mainly to control the amount of carbon coated in the negative electrode material after high-temperature calcination, so as to improve the conductivity of the material without significantly reducing the compaction density of the material.

[0049] In the above step 3, the calcination temperature is 700-1100° C., and the calcination time is 2-10 hours. The resin material is carbonized by high-temperature calcination, and the resin is converted into carbon under the protection of an inert gas.

[0050] In the above step 3, the carbon content of the sodium titanium phosphate / carbon composite material is 2-25%, for example 5%, 10%, 15%, 20%; controlling the carbon content within this range can not only increase the conductivity of the negative electrode material, but also ensure that the compaction density of the sodium titanium phosphate / carbon composite material is not too low.

[0051] It should be noted that in the above step 3, the D50 (median particle size) of the negative electrode active material is 4-15µm. Controlling the median particle size D50 of the negative electrode material within the range of 4-15µm can make the particle size of the negative electrode active material have a suitable particle size distribution. The small particles in the system can fill the gaps in the large particles, which helps to increase the compaction density of the electrode sheet, thereby improving the volume energy density of the battery.

[0052] Compared with the prior art, firstly, the present invention adopts a dry coating process to carbon-coat the negative electrode material, and after firing, the coating layer is tightly combined with the negative electrode material and is not easy to fall off.

[0053] Secondly, the present invention improves the conductivity of sodium titanium phosphate by coating the carbon layer.

[0054] Third, the present invention ensures the uniformity of carbon coating by mixing the sodium titanium phosphate precursor with the thermosetting resin at a high speed, thereby ensuring the uniformity of the carbon layer on the surface of the negative electrode material after calcination.

[0055] Fourth, compared with the traditional wet electrode, the dry electrode of the present invention omits the drying and curing process, thereby shortening the production cycle and reducing the production cost; in addition, the binder in the dry electrode exists in a fibrous state, and the binder is only in point contact with the surface of the active material particles, which does not affect the internal contact between the active material particles. The contact between the active material particles and with the conductive agent particles is closer, and the resistance is smaller.

[0056] On the other hand, the present invention further provides a negative electrode active material, which is prepared by the above-mentioned method for preparing the negative electrode active material.

[0057] Furthermore, the present invention also provides a method for preparing a dry electrode sheet, wherein the dry electrode sheet is a dry negative electrode sheet or a positive electrode sheet, comprising the following steps:

[0058] Step 1: Mix the positive electrode active material or negative electrode active material of the dry electrode with the conductive agent and the binder in a certain proportion, then add them into the fiberizing equipment, and obtain highly fiberized electrode powder after high-speed shearing treatment;

[0059] In the above step 1, the mass mixing ratio of the positive electrode active material or the negative electrode active material to the conductive agent and the binder of the dry electrode is (85-90): (8-10): (2-5), for example, 90:8:2, 81:10:9, 87:8:5, 86:9:5, 90:7:3.

[0060] In the above step 1, the positive electrode active material is one or more of sodium vanadium phosphate, sodium manganese titanium phosphate, lithium manganate, and sodium manganate.

[0061] In the above step 1, the conductive agent includes one or more of graphite, conductive carbon black, acetylene black, carbon fiber, and carbon nanotubes; and the binder is PTFE powder.

[0062] In the above step 1, the shearing or stirring rate is 4500-15000 r / min, and the shearing time is 15-45 min. The purpose of controlling the above shearing rate and stirring time is to fully fiberize the PTFE.

[0063] Step 2, extruding the highly fibrous electrode powder at a temperature of 50-200°C to form an initial dry electrode membrane;

[0064] In the above step 2, the thickness of the obtained initial dry electrode membrane is 200-300 μm, for example, 210 μm, 240 μm, 260 μm, 280 μm.

[0065] Step 3, rolling the initial dry electrode membrane to obtain a dry electrode membrane;

[0066] In the above step 3, the rolling pressure is 5-25T, the rolling temperature is 30-110°C, and the thickness of the dry electrode membrane after rolling is 100-200μm. The purpose of rolling treatment is to reduce the thickness of the initial electrode membrane and increase its surface density; the thickness of the dry electrode membrane is reduced, the wetting effect between the electrode material and the electrolyte is better, and the rate performance is increased.

[0067] Step 4: hot rolling composite the above dry electrode membrane and the current collector, the hot rolling temperature is 90-200°C, the hot rolling pressure is 5-25T, to form a dry electrode, the thickness of the dry electrode is 115-250μm.

[0068] In the above step 4, the hot rolling temperature is 90-200° C. Controlling the hot rolling temperature within this range can improve the bonding strength between the dry electrode membrane and the current collector.

[0069] In the above step 4, in order to reduce the interface impedance of the current collector, the current collector is made of one or more of stainless steel foil, stainless steel mesh, aluminum foil, and carbon-coated aluminum foil.

[0070] In order to further reduce the interface impedance of the current collector, in the above step 4, the current collector is a carbon-coated aluminum foil, and the preparation process of the carbon-coated aluminum foil includes:

[0071] Step 41, cleaning the aluminum foil;

[0072] Use deionized water, ethanol or acetic acid to remove dust, oil and impurities on the surface of the aluminum foil.

[0073] Step 42: preparing a conductive composite slurry;

[0074] The binder and the solvent are mixed evenly, and then the conductive agent is added and mixed evenly to obtain a conductive composite slurry; the solid content of the conductive composite slurry is 20%-40%, the mass proportion of the conductive agent is 3-15%, and the mass proportion of the binder is 1-5%; wherein the binder is one or more of PVDF, PTFE, PVA, and PAA; the conductive agent is one or more of graphene, conductive carbon black, carbon nanotubes, and hard carbon; the solvent is one or more of deionized water, ethanol, and N,N-dimethylformamide.

[0075] Step 43: coat the conductive composite slurry on the aluminum foil by blade coating, and dry it at 80-120° C. for 2-8 h (eg, 3 h, 5 h, 7 h) to obtain a conductive coating with a thickness of 1-4 μm.

[0076] The carbon-coated aluminum foil prepared by the present invention can reduce the interface impedance of the current collector, reduce polarization, and improve the cycle life and rate performance.

[0077] In a fourth aspect, the present invention further provides a dry electrode, which is prepared by the above-mentioned dry electrode preparation method, and the dry electrode includes a positive electrode sheet and a negative electrode sheet.

[0078] In a fifth aspect, the present invention also provides an aqueous battery, which includes a dry electrode, an electrolyte and a battery casing; wherein the electrolyte is a sodium salt aqueous solution, and the sodium ion concentration in the sodium salt aqueous solution is 1-2M to ensure a larger ionic conductivity.

[0079] Compared with the prior art, the aqueous sodium ion battery of the present invention uses a dry coating method to carbon-coat the material, which shortens the synthesis time of the electrode material. In addition, the dry manufacturing process is used to prepare the electrode. The dry electrode is solvent-free and can avoid electrode stratification during the drying process. In the dry manufacturing process, the binder exists in a fibrous state and is in point contact with the active material, which does not affect the contact between the active material and the conductive agent, and has better conductivity. Compared with the wet electrode, the dry electrode omits the drying step, reducing production costs.

[0080] Example 1

[0081] Preparation process of negative electrode: nano titanium dioxide, ammonium dihydrogen phosphate and sodium carbonate are mixed evenly in a molar ratio of 2:3:1.05, and the obtained mixed solution is spray-dried to obtain a sodium titanium phosphate precursor; the precursor powder and epoxy resin are mixed at a high speed in a mass ratio of 85:15, and the epoxy resin-coated sodium titanium phosphate precursor is calcined at 1000°C for 4h under a nitrogen atmosphere to obtain NTP / C, whose XRD pattern is shown in Figure 1 and its SEM pattern is shown in Figure 2. Figure 2 shown.

[0082] NTP / C is uniformly mixed with conductive carbon black, graphite and PTFE in a mass ratio of 85:6:4:5, and a high-speed shearing treatment is performed using a fiberizing device. The shearing or stirring rate is 6000r / min, and the shearing or stirring time is 30min. A uniformly mixed highly fiberized electrode powder is obtained, in which the PTFE is fully fiberized. The fiberized powder is extruded by a twin-screw extruder at an extrusion temperature of 60°C to form an initial membrane. The initial membrane is further rolled at a rolling temperature of 30°C to obtain a dry electrode membrane with a thickness of 100μm. The dry electrode membrane is compounded with aluminum foil by hot rolling to obtain an aqueous sodium ion battery negative electrode sheet.

[0083] Preparation process of positive electrode sheet: Li2Mn2O4, conductive carbon black and PTFE are mixed evenly in a mass ratio of 86:9:5, and high-speed shearing treatment is performed using fiberizing equipment. The shearing or stirring rate is 5000r / min, and the shearing or stirring time is 15min. The obtained mixed and highly fiberized electrode powder is fully fiberized. The fiberized powder is extruded by a twin-screw extruder at an extrusion temperature of 60°C to form an initial membrane. The initial membrane is further rolled at a rolling temperature of 30°C to obtain a dry electrode membrane with a thickness of 100μm. The dry electrode membrane is compounded with aluminum foil by hot rolling to obtain an aqueous sodium ion battery positive electrode sheet.

[0084] The above NTP / C negative electrode was used in combination with the Li2Mn2O4 positive electrode to assemble a battery, and the electrochemical performance was tested at a current of 80 mA / g in the voltage range of 1-1.9 V. Figure 4 As shown, the initial capacity of the full battery assembled in this embodiment is 81.7 mAh / g, and the capacity retention rate is 95% after 200 cycles, and the cycle stability is good.

[0085] Comparative Example 1

[0086] Nano titanium dioxide, ammonium dihydrogen phosphate and sodium carbonate were mixed uniformly in a molar ratio of 2:3:1.05, sucrose, conductive carbon black and graphite were added to the mixed solution in a mass ratio of 2:1:1, sucrose, conductive carbon black and graphite accounted for 20% of the final product, the obtained mixed solution was spray dried to obtain sodium titanium phosphate / carbon precursor, the precursor was placed in a nitrogen atmosphere, calcined at 750℃ for 12h to obtain NTP / C. NTP / C was mixed uniformly with conductive carbon black, graphite and PTFE in a mass ratio of 85:6:4:5, the PTFE was fully fiberized by high-speed shearing treatment to obtain a uniformly mixed dry powder, the fiberized powder was extruded by a twin-screw extruder to form an initial membrane, the initial membrane was further rolled to obtain an electrode membrane, and the electrode membrane was compounded with aluminum foil by hot rolling to obtain an aqueous sodium ion battery negative electrode.

[0087] Preparation method of positive electrode sheet: Li2Mn2O4, conductive carbon black and PTFE are mixed evenly in a mass ratio of 86:9:5, and the PTFE is fully fiberized by high-speed shearing treatment to obtain a uniformly mixed dry powder. The fiberized powder is extruded by a twin-screw extruder to form an initial membrane, and the initial membrane is further rolled to obtain an electrode membrane. The electrode membrane is compounded with aluminum foil by hot rolling to obtain an aqueous sodium ion battery positive electrode sheet.

[0088] The cycle performance of the aqueous sodium ion battery composed of the dry electrode prepared in Example 1 was compared with that of the aqueous sodium ion battery composed of the wet electrode prepared in Comparative Example 1. Figure 3 As shown, it can be seen that the stability of the battery composed of NTP / C obtained by dry coating with resin as the carbon source is significantly better than that of the battery composed of NTP / C obtained by wet coating.

[0089] Example 2

[0090] This embodiment provides a preparation method of a dry electrode, which is basically the same as that of Embodiment 1, except that the selected resin material is thermosetting polyimide, and the coated sodium titanium phosphate material is calcined at 950° C. for 2 h in a nitrogen atmosphere to obtain NTP / C.

[0091] The above NTP / C negative electrode was used with the Li2Mn2O4 positive electrode to assemble a battery, and the electrochemical performance was tested at a current of 80mA / g in the voltage range of 1.9V. The results are as follows Figure 4 shown.

[0092] Comparative Example 2

[0093] Nano titanium dioxide, ammonium dihydrogen phosphate and sodium carbonate were mixed evenly in a molar ratio of 2:3:1.05, and the obtained mixed solution was spray-dried to obtain a sodium titanium phosphate precursor; the precursor powder was mixed with epoxy resin at a mass ratio of 85:15 at a high speed, and the resin-coated sodium titanium phosphate precursor was calcined at 1000°C for 2h under a nitrogen atmosphere to obtain NTP / C. NTP / C was mixed evenly with conductive carbon black, graphite and PTFE in a mass ratio of 85:6:4:5 in deionized water to obtain a negative electrode slurry, and the slurry was evenly coated on an aluminum current collector and dried at 80°C for 12h to obtain an aqueous sodium ion battery negative electrode sheet.

[0094] Preparation method of positive electrode sheet: Li2Mn2O4, conductive carbon black and PTFE are mixed evenly in deionized water in a mass ratio of 86:9:5 to obtain positive electrode slurry, the slurry is evenly coated on the aluminum current collector, and dried at 80°C for 12 hours to obtain the positive electrode sheet of the aqueous sodium ion battery.

[0095] The cycle performance of the aqueous sodium ion battery composed of the dry electrode of Example 2 was compared with that of the aqueous sodium ion battery composed of the wet electrode of Comparative Example 2. Figure 4 As shown, it can be seen that the battery capacity obtained by dry electrode assembly in Example 2 is significantly higher than that of the battery obtained by wet electrode assembly in Comparative Example 2. This indicates that the binder in the dry electrode exists in a fibrous state and is in point contact with the active material, which does not affect the contact between the active material and the conductive agent, thereby enabling the active material to perform better.

[0096] Example 3

[0097] This embodiment provides a preparation of a dry electrode, which is basically the same as Embodiment 1, except that the mass ratio of NTP / C to conductive carbon black, graphite and PTFE is 90:5:2:3; the mass ratio of the positive electrode sheet Li2Mn2O4, conductive carbon black and PTFE is 90:7:3.

[0098] Example 4

[0099] This embodiment provides a dry electrode preparation method, and the negative electrode dry electrode sheet preparation method is the same as that of embodiment 3. The difference is that the positive electrode sheet of this embodiment is prepared by a wet process.

[0100] Preparation method of positive electrode sheet: Li2Mn2O4, conductive carbon black and PTFE are mixed in deionized water at a mass ratio of 86:9:5 to obtain positive electrode slurry, and the slurry is evenly coated on the aluminum current collector and dried at 80℃ for 12h to obtain the positive electrode sheet of aqueous sodium ion battery. The above sheets are assembled into batteries and the rate performance is tested in the voltage range of 1-1.9V. The results are as follows: Figure 5 shown.

[0101] Example 5

[0102] This embodiment provides a preparation of a dry electrode, and the positive electrode dry electrode is the same as that of embodiment 3. The difference is that the negative electrode of this embodiment is prepared by a wet process. The preparation method of the negative electrode is as follows: the preparation process of the negative electrode: nano titanium dioxide, ammonium dihydrogen phosphate, and sodium carbonate are uniformly mixed in a molar ratio of 2:3:1.05, and the obtained mixed solution is spray-dried to obtain a sodium titanium phosphate precursor; the precursor powder and the epoxy resin are mixed at a high speed in a mass ratio of 85:15, and the epoxy resin-coated sodium titanium phosphate precursor is calcined at 1000°C for 4h under a nitrogen atmosphere to obtain NTP / C.

[0103] NTP / C was mixed with conductive carbon black, graphite and PTFE in a mass ratio of 90:5:2:3 in deionized water to obtain negative electrode slurry. The slurry was evenly coated on the aluminum current collector and dried at 80℃ for 12h to obtain the negative electrode plate of the aqueous sodium ion battery. The above plates were assembled into a battery and the rate performance was tested in the voltage range of 1-1.9V. The results are as follows: Figure 5 shown.

[0104] The negative electrode prepared by the above method and the positive electrode prepared by the above method were assembled into a battery, and the rate performance was tested in the voltage range of 1-1.9V. The results are as follows Figure 5 shown.

[0105] The coulombic efficiency (99.5%-99.8%), cycle performance (92%-95%), and rate performance (83%-86%) of the aqueous sodium ion battery assembled with the dry electrode prepared by the NTP / C prepared by the dry coating process in Examples 1-3 are better than the battery performance in Comparative Examples 1-2, as shown in Table 1 below; the coulombic efficiency and cycle performance of the aqueous sodium ion battery assembled with the dry electrode prepared by the NTP / C prepared by the dry coating process in Examples 1-2 are better than the battery performance in Comparative Examples 1-2, and according to the rate performance comparison of Examples 3, 4, and 5, the battery capacity with dry electrode sheets for both positive and negative electrodes is better than that with dry electrodes on one side, and when the current increases to 2C, the battery capacity retention rate of Example 3 is 80%, which is better than that of Examples 4 and 5.

[0106] Table 1 Comparison of battery performance in Examples 1 to 3 and battery performance in the comparative example

[0107]

[0108] The present invention uses a dry coating method to carbon-coat NTP, shortening the synthesis time of electrode materials, and adopts a dry manufacturing process to prepare electrodes. The dry electrode is solvent-free and can avoid electrode stratification during the drying process. In the dry manufacturing process, the binder exists in a fibrous state, and the binder is in point contact with the active material, which does not affect the contact between the active material and the conductive agent, and has better conductivity. Compared with the wet electrode, the dry electrode omits the drying step, reducing production costs and improving production efficiency.

[0109] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A dry method for preparing negative electrode active materials for aqueous sodium batteries, characterized in that: The negative electrode active material is a sodium titanium phosphate / carbon composite material; the preparation process of the sodium titanium phosphate / carbon composite material comprises the following steps: Step 1, preparing a sodium titanium phosphate precursor; In step 1, the preparation process of the sodium titanium phosphate precursor includes: The titanium source, the phosphate source and the sodium source are uniformly mixed by ball milling in a molar ratio of 2:3:(1-1.05) to obtain a precursor suspension, and the precursor suspension is spray-dried to obtain a sodium titanium phosphate precursor; In step 1, the solid content of the precursor suspension is 15-30%; Step 2, coating the sodium titanium phosphate precursor with resin; The obtained sodium titanium phosphate precursor is mixed with a thermosetting resin at a high speed to obtain a resin-coated sodium titanium phosphate precursor; In step 2, the sodium titanium phosphate precursor and the thermosetting resin are mixed for 10-45 min, and the stirring speed during mixing is 3000-7000 rad / min to obtain a resin-coated sodium titanium phosphate precursor; In step 2, the thermosetting resin is an epoxy resin; the mass ratio of the epoxy resin, i.e., the percentage of the thermosetting resin material in the total mass of the sodium titanium phosphate precursor and the resin material, is 15%; Step 3, calcining the resin-coated sodium titanium phosphate precursor in an inert gas at a high temperature to obtain a sodium titanium phosphate / carbon composite material; In step 3, the calcination temperature is 1000° C. and the calcination time is 4 hours. The resin material is carbonized by high-temperature calcination, and the resin is transformed into carbon under the protection of an inert gas. In step 3, the carbon content of the sodium titanium phosphate / carbon composite material is 2-25%.

2. The dry method for preparing the negative electrode active material of aqueous sodium battery according to claim 1, characterized in that: In step 1, the titanium source is one or more of titanium dioxide, tetrabutyl titanate, isopropyl titanate, titanium phosphate, and titanium tetrachloride.

3. The dry method for preparing the negative electrode active material of aqueous sodium battery according to claim 1, characterized in that: In step 1, the phosphate source is one or more of NaH2PO4, diammonium phosphate, titanium phosphate, and phosphoric acid.

4. The dry method for preparing the negative electrode active material of aqueous sodium battery according to claim 1, characterized in that: In step 1, the sodium source is one or more of Na2CO3, NaH2PO4, NaHCO3, and CH3COONa.

5. The dry method for preparing negative electrode active materials for aqueous sodium batteries according to claim 1, characterized in that: In step 3, the D50 of the negative electrode active material is 4-15 μm.

6. An aqueous sodium battery negative electrode active material, characterized in that: The negative electrode active material is prepared by the dry preparation method of any one of claims 1 to 5.

7. A dry-process negative electrode sheet for an aqueous sodium battery, characterized in that: The negative electrode active material is prepared by the dry method for preparing the negative electrode active material according to any one of claims 1 to 5; Alternatively, it is prepared using the negative electrode active material described in claim 6.

8. An aqueous battery, characterized in that: It comprises the negative electrode dry-process electrode sheet of the aqueous sodium battery as described in claim 7; and also comprises a positive electrode dry-process electrode sheet, an electrolyte and a battery casing.

Citation Information

Patent Citations

  • Preparation method of lithium titanium phosphate anode material

    CN106299267A

  • Preparation method of nitrogen-doped carbon-coated dual-core shell lithium titanium phosphate or sodium titanium phosphate

    CN107910514A

  • A core-shell structure negative electrode material for lithium ion battery and preparation method thereof are provided

    CN108987730A

  • Aqueous lithium / sodium ion battery based on nickel hydroxide positive electrode and titanium-based ion embedded negative electrode

    CN115133145A

  • Method for preparing aqueous sodium-ion battery by dry method

    CN115579530A